AN EXPLORATION OF THE NEW AVENUES FOR ANALYSING RELIGIOUS EXPERIENCE - Ouseparampll, Joseph (Journal of Dharma, 1980)
Religious experiences are at the same time fascinating and’ mystic.’ Many kinds of experiences have been reported to us from Vedic age onwards. The seeming contradictions in them are only apparent. All the ancient and recent mystics hold that they have tradition and scriptures to support them. Various methods employed to analyse and understand the experiences proved to be unsuccessful. Aesthetic experiences are akin to religious experiences and they have been analysed and studied in India. Hence an attempt is made here to see whether an aesthetico-metaphysical.